Surface hydrolysis of polyamide with a new polyamidase from Beauveria brongniartii - Almansa, Eva (2008)
Twelve fungi were screened for the potential of their extracellular enzymes to increase the hydrophilicity of polyamide (PA) materials. The most pronounced increase in hydrophilicity was found for enzymes from Beauveria brongniartii and B. bassiana. The 55 kDa polyamidase from B. brongniartii was purified using ultrafiltration, anion exchange chromatography and size exclusion chromatography. This polyamidase was able to hydrolyse adipic acid bishexylamide and various typical amidase substrates, but did not show protease activity. In contrast, the 27 kDa protease from B. brongniartii did not show activity on PA. The improvement of hydrophilicity due to hydrolysis with the 55 kDa polyamidase from B. brongniartii based on rising height was 11 cm for PA 6 Perlon fibres and 5 cm for PA 6.6 Nylon. The drop dissipation measurement corroborated the improvement of the hydrophilicity giving 7 s and less than 1 s for the two enzyme treated materials, respectively. The surface tension s of Perlon increased from 46.1 to 67.4 mNm after enzyme treatment.